1 - (sin^2 x/1+cot x) - (cos^2 x/1+tan x) = sin x cos x
1 - (sin^2 x/(1+(cos x/sin x))) - (cos^2 x/(1+(sin x/cos x))) = sin x cos x
1 - (sin^2 x/((sin x/sin x)+(cos x/sin x))) - (cos^2 x/((cos x/cos x)+(sin x/cos x))) = sin x cos x
1 - (sin^2 x/((1/sin x)*(sin x+cos x))) - (cos^2 x/((1/cos x)*(cos x+sin x))) = sin x cos x
1 - (sin^3 x/(sin x+cos x)) - (cos^3 x/(cos x+sin x)) = sin x cos x
Factor out -1 and then combine the two fractions (which can now be added)...
1 - ((sin^3 x+cos^3 x)/(sin x+cos x)) = sin x cos x
Because sin^2 x + cos^2 x = 1...
(sin^2 x + cos^2 x) - ((sin^3 x+cos^3 x)/(sin x+cos x)) = sin x cos x
Multiply out the two terms...
((sin x + cos x)(sin^2 x + cos^2 x))/(sin x + cos x) - ((sin^3 x+cos^3 x)/(sin x+cos x)) = sin x cos x
(sin^3 x + sin x cos^2 x + sin^2 x cos x + cos^3 x)/(sin x + cos x) - ((sin^3 x+cos^3 x)/(sin x+cos x)) = sin x cos x
(sin^3 x + sin x cos^2 x + sin^2 x cos x + cos^3 x - sin^3 x - cos^3 x)/(sin x+cos x)) = sin x cos x
(sin x cos^2 x + sin^2 x cos x)/(sin x+cos x)) = sin x cos x
Factor out sin x
(sin x*(cos^2 x + sin x cos x))/(sin x+cos x)) = sin x cos x
Factor out cos x
((sin x cos x)*(cos x + sin x))/(sin x+cos x)) = sin x cos x
The numerator and denominator now cancel out, and thats it.
sin x cos x) = sin x cos x
That's all I can give man, its screwing with my brain to write all that math. Granted, I haven't taken trigonometry, or done a proof in probably 8 years, all of that could be wrong.